1999
DOI: 10.1590/s1415-47571999000200001
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous ethnic distribution of the factor v leiden mutation

Abstract: Inherited resistance to activated protein C caused by the factor V Leiden (FVL) mutation is the most common genetic cause of venous thrombosis yet described, being found in 20-60% of patients with venous thrombophilia. A relationship between the FVL mutation and an increased predisposition to arterial thrombosis in young women was recently reported. We assessed the prevalence of the FVL mutation in 440 individuals (880 chromosomes) belonging to four different ethnic groups: Caucasians, African Blacks, Asians a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
2
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
1
6
2
2
Order By: Relevance
“…In our study the observed FVL G1691A frequency (1.6%) did not differ significantly from the frequencies observed in most of Caucasian populations (Adamczuk et al, 2000) or from that reported by Franco et al (1999) in Brazilians of European origin (1.3%) and Brazilian Amerindians (0.3%), but was significantly lower than the 6.9% found in Greeks (Angelopoulou et al, 2000).…”
contrasting
confidence: 64%
“…In our study the observed FVL G1691A frequency (1.6%) did not differ significantly from the frequencies observed in most of Caucasian populations (Adamczuk et al, 2000) or from that reported by Franco et al (1999) in Brazilians of European origin (1.3%) and Brazilian Amerindians (0.3%), but was significantly lower than the 6.9% found in Greeks (Angelopoulou et al, 2000).…”
contrasting
confidence: 64%
“…The fact that the mutation is rarely seen in other regions of the world but it is highly frequent in Europe makes the matter worth examining. 3,4,[16][17][18][19][20][21][22] The alteration among different ethnic groups suggests that the FVL came about after the separation of Mongoloids and Caucasians. 18 This idea gives rise to the conclusion that a point mutation occurred recently in the founder population of Europe and was spread throughout the continent by migration.…”
Section: Discussionmentioning
confidence: 99%
“…Factor V Leiden mutation is the most frequent inherited risk factor for VTE, with a prevalence of 5% in the general Caucasian population and a much higher frequency in the Greek Cypriot and southern Sweden population, up to 13.3% (7,8). In the African and Asian populations this mutation is very rare (9). In the general Caucasian population the prevalence of FV Leiden mutation is 20-50% among patients with DVT.…”
Section: Introductionmentioning
confidence: 99%